Evaluating Sagittal Balance with Lumbopelvic Parameters: A Single-Center Performance Improvement Project. Issue 1 (April 2016) - Chiappini, Alessio; Cunningham, Michael; Mariani, Luigi; Jost, Gregory
Introduction: Neutral sagittal balance is key for painless upright posture and a large offset of sagittal balance may cause low back pain and correlates with impaired quality of life. Lumbar sagittal balance can easily be assessed on a standing X-ray, however, it is still a new concept to many spine specialists and radiologists. Materials and Methods: A performance improvement program was developed to enable radiologists and neurosurgeons to quickly assess lumbar sagittal balance. Baseline knowledge and reporting were analyzed. Clinical tools to measure lumbar sagittal balance were taught with a 30-minute presentation. Following this, a spine surgeon helped colleagues measure their first patients. Results: At baseline, 42% of 75 patients showed problems with lumbar sagittal balance but basic knowledge of sagittal balance was low: only 10% of pre- and post-treatment X-ray reports and only 1% of neurosurgical reports included information on sagittal balance. The 30-minute presentation empowered the target audience with the clinical skills to measure, interpret, and report lumbar sagittal balance on a standing X-ray. Intermittent encouragement and support from a spine surgeon helped colleagues to evaluate lumbar sagittal balance in their patients. In the first three months following the presentation, the neurosurgeons documented pelvic parameters in 48% of patients (14 of 29) and the radiologists reported the pelvic parameters on all new lumbar X-rays. Assessing and reporting sagittal balance has become a routine procedure beyond the study period and has led to more profound understanding of deformity induced pain and disability, not only by doctors, but also by patients to whom the origin of their back pain can be explained. Conclusions: A short teaching presentation on a poorly known yet important clinical concept enables radiologists and spine specialists to easily measure and interpret heretofore underused information from the standing lumbar X-ray. Performance improvement programs are a valuable educational intervention for surgeons and to engage teams in interdisciplinary learning.